Elderly friendly design of public sign: User experience - Xiong Ding; Teddy Marius Soikun (ASR Research India, 2022)
As the world enters an aging society, the construction of an elderly-friendly society and the designer to pay attention to the elderly are particularly important. Public signs system directly affects the good experience of the elderly in the process of going out, seeking medical treatment, and traveling. From the perspective of elderly user experience and Pierce Semiotics’ classification of signs as the theoretical basis, this research combines the Kansei Engineering (typeI) method and the Formalistic and Visual Semiotic Analysiswhich processing formal properties of art and design, to get the sign features and forms that loved by elderly, and three aspects hypothesis that affect elderly choose the sign.